Probing Biosensing Interfaces With Single Molecule Localization Microscopy (SMLM) - Cheng, Xiaoyu; Yin, Wei (Frontiers in Chemistry, 2021)
Far field single molecule localization microscopy (SMLM) has been established as a powerful tool to study biological structures with resolution far below the diffraction limit of conventional light microscopy. In recent years, the applications of SMLM have reached beyond traditional cellular imaging. Nanostructured interfaces are enriched with information that determines their function, playing key roles in applications such as chemical catalysis and biological sensing. SMLM enables detailed study of such interfaces at individual molecular level, allowing measurements of reaction kinetics, and detection of rare events in complex environments. Such capability lays the foundation to the development of using SMLM to probe biointerfaces. This paper provides an update to the progresses of using of SMLM in characterizing nanostructured biointerface, focusing on practical aspects, recent advances and emerging opportunities from an analytical science perspective.